Cult Places and Cultural Change in Republican Italy : A Contextual Approach to Religious Aspects of Rural Society after the Roman Conquest - Stek, Tesse D. (2010)
This scholarly study throws a new light on the Roman impact on religious structures in Republican Italy. In the last four centuries BC, Italy went through immense changes. The Apennine and Adriatic areas were originally inhabited by various 'Italic' tribes and characterised by a specific non-urban societal organisation, in which cult places had a pivotal function. From the fourth century BC onwards the area was gradually incorporated by Rome, profoundly altering its geopolitical make-up. The author not only investigates the changing social and political function of cult places in non-Roman Italic society, he also highlights the importance of cult places and religious rituals for new Roman communities in the conquered areas. This research thus opens new perspectives on the issue of the 'religious romanisation' of Italy by arguing for a strong Roman impact also in non-urbanised areas. Tesse Stek bases his study on the analysis of archaeological, literary and epigraphic evidence from rural cult places in Central and Southern Italy, including field work on the Samnite temple of S. Giovanni in Galdo.